Shape-memory responses compared between random and aligned electrospun fibrous mats - Wang, Xianliu; Zhang, Zhaowenbin; Qin, Chunping; Guo, Xuran; Zhang, Yanzhong (Frontiers in Bioengineering and Biotechnology, 2023)
Significant progress has been made in the design of smart fibers toward achieving improved efficacy of tissue regeneration. While the electrospun fibers can be engineered with a shape memory capability, both the fiber structure and applied shape-programming parameters are the determinants of final performance in applications. Herein, we report a comparison study on the shape memory responses compared between electrospun random and aligned fibers by varying the programming temperature Tprog and the deforming strain edeform. A PLLA-PHBV (6:4 mass ratio) polymer blend was firstly electrospun into random and aligned fibrous mat forms; thereafter effects of applying specific Tprog (37 ℃ and 46 ℃) and edeform (30%, 50% and 100%) on the morphological change, shape recovery efficiency, and switching temperature Tsw of the two types of fibrous structures were examined under stress-free condition, while the maximum recovery stress max was determined under constrained recovery condition. It was identified that the applied Tprog had less impact on fiber morphology, but increasing edeform gave rise to attenuation in fiber diameters and bettering in fiber orientation, especially for the random one. The efficiency of shape recovery was found to correlate with both the applied Tprog and edeform, with the aligned fibers exhibiting relatively higher recovery ability than the random counterpart. Moreover, Tsw was observed to be close to the Tprog thereby revealing a temperature memory effect in the PLLA-PHBV fibers with the aligned showing a more proximity, while the max generated was edeform dependent and 2.13.4 folds of stronger for the aligned in comparison with the random. Overall, the aligned fibers generally demonstrated better shape memory properties, which can be attributed to the macroscopic structural orderliness and increased molecular orientation and crystallinity imparted during the shape-programming process. Finally, the feasibility of using shape memory effect-enabled mechanoactive fibrous substrate for regulating osteogenic differentiation of stem cells was demonstrated with the use of aligned fibers.